Epithelial Barrier Dysfunction in Chronic Respiratory Diseases - Carlier, François M.; de Fays, Charlotte; Pilette, Charles (Frontiers in Physiology, 2021)
Mucosal surfaces are lined by epithelial cells, which provide a complex and adaptive module that ensures first line defense against external toxics, irritants, antigens, and pathogens. The underlying mechanisms of host protection encompass multiple physical, chemical, and immune pathways. In the lung, inhaled agents continually challenge the airway epithelial barrier, which is altered in chronic diseases such as chronic obstructive pulmonary disease, asthma, cystic fibrosis, or pulmonary fibrosis. In this review, we describe the epithelial barrier abnormalities that are observed in such disorders and summarize current knowledge on the mechanisms driving impaired barrier function, which could represent targets of future therapeutic approaches.